2013
DOI: 10.1016/s1734-1140(13)71502-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nifedipine on the pharmacokinetics of repaglinide in rats: Possible role of CYP3A4 and P-glycoprotein inhibition by nifedipine

Abstract: Nifedipine enhanced the oral bioavailability of repaglinide, which may be mainly attributable to inhibition of CYP3A4-mediated metabolism of repaglinide in the small intestine and/or in the liver and to inhibition of the P-gp efflux transporter in the small intestine and/or reduction of total body clearance by nifedipine. The current study has raised awareness of potential drug interactions by concomitant use of repaglinide with nifedipine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…ABCB1, also known as P-glycoprotein, has been shown to play an important role in drug efflux 32) . Previous studies showed that resveratrol inhibited P-glycoprotein activity both in vitro 33) and in vivo 34) models. However, it is reported that the absorption of warfarin was independent of P-glycoprotein activity 35) .…”
Section: Discussionmentioning
confidence: 95%
“…ABCB1, also known as P-glycoprotein, has been shown to play an important role in drug efflux 32) . Previous studies showed that resveratrol inhibited P-glycoprotein activity both in vitro 33) and in vivo 34) models. However, it is reported that the absorption of warfarin was independent of P-glycoprotein activity 35) .…”
Section: Discussionmentioning
confidence: 95%
“…For example, Choi et al found that RESV significantly reduced rhodamine123 efflux via P-gp in MCF-7/ADR cells that overexpress P-gp, and significantly increased the drug exposure of orally administered nicardipine in rats 28. In contrast, Yang et al reported that RESV exerted a stimulatory effect on P-gp, resulting in a reduction of cyclosporine oral bioavailability in rats 15.…”
Section: Discussionmentioning
confidence: 99%
“…The small intestine is an important organ in the pharmacokinetics of orally administered drugs owing to the presence of drug transporters and drug-metabolizing enzymes (Choi et al, 2013;Li et al, 2013;Yoshida et al, 2013;Kostewicz et al, 2014). Thus, Caco-2 cells, a human colon carcinoma cell line, are widely used to evaluate the intestinal transport of orally administered drugs.…”
Section: Introductionmentioning
confidence: 99%